Evaluation of piggyBac‐mediated anti‐CD19 CAR‐T cells after ex vivo expansion with aAPCs or magnetic beads. Issue 2 (22nd November 2020) - Yang, Li‐Rong; Li, Lin; Meng, Ming‐Yao; Wang, Wen‐Ju; Yang, Song‐Lin; Zhao, Yi‐Yi; Wang, Run‐Qing; Gao, Hui; Tang, Wei‐Wei; Yang, Yang; Yang, Li‐Li; Liao, Li‐Wei; et al.
Abstract: Adoptive immunotherapy is a new potential method of tumour therapy, among which anti‐CD19 chimeric antigen receptor T‐cell therapy (CAR‐T cell), is a typical treatment agent for haematological malignancies. Previous clinical trials showed that the quality and phenotype of CAR‐T cells expanded ex vivo would seriously affect the tumour treatment efficacy. Although magnetic beads are currently widely used to expand CAR‐T cells, the optimal expansion steps and methods have not been completely established. In this study, the differences between CAR‐T cells expanded with anti‐CD3/CD28 mAb‐coated beads and those expanded with cell‐based aAPCs expressing CD19/CD64/CD86/CD137L/mIL‐15 counter‐receptors were compared. The results showed that the number of CD19‐specific CAR‐T cells with a 4‐1BB and CD28 co‐stimulatory domain was much greater with stimulation by aAPCs than that with beads. In addition, the expression of memory marker CD45RO was higher, whereas expression of exhausted molecules was lower in CAR‐T cells expanded with aAPCs comparing with the beads. Both CAR‐T cells showed significant targeted tumoricidal effects. The CAR‐T cells stimulated with aAPCs secreted apoptosis‐related cytokines. Moreover, they also possessed marked anti‐tumour effect on NAMALWA xenograft mouse model. The present findings provided evidence on the safety and advantage of two expansion methods for CAR‐T cells genetically modified by piggyBac transposon system.